2019
DOI: 10.1111/eos.12662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silencing of mediator of DNA damage checkpoint protein 1 on the growth of oral squamous cell carcinoma in vitro and in vivo

Abstract: Effect of silencing of mediator of DNA damage checkpoint protein 1 on the growth of oral squamous cell carcinoma in vitro and in vivo. Eur J Oral Sci 2019; 127: 494-499. © 2019 Eur J Oral SciMediator of DNA damage checkpoint protein 1 (MDC1) is involved in DNA damage repair and has been linked to tumor invasion, metastasis, and prognosis. This study investigated the effects of MDC1 in oral squamous cell carcinoma (OSCC) in vitro and in vivo. RNA interference-mediated knockdown of MDC1 was performed in two OSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Transwell assays were performed as previously described [ 27 ]. Briefly, the Transwell chambers were uncoated for evaluation of cell migration capabilities, or pre-coated with 80 μL Matrigel (BD, USA) for 30 min for evaluation of cell invasion capabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Transwell assays were performed as previously described [ 27 ]. Briefly, the Transwell chambers were uncoated for evaluation of cell migration capabilities, or pre-coated with 80 μL Matrigel (BD, USA) for 30 min for evaluation of cell invasion capabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the expression of Mre11 in oral cancer tissues is significantly higher than that in adjacent noncancerous oral tissues and that oral cancers with high MRE11 expression have reduced OS and progression-free survival (42). In addition, the mediator of DNA damage checkpoint protein 1 (MDC1) is associated with the recruitment of DNA damage repair proteins to the site of DSBs (65). Clinical studies have shown that in OSCC (100 patients), nuclear and cytoplasmic MDC1 protein expression levels were 85% and 92%, respectively.…”
Section: Dna Damage Repair In Hnsccmentioning
confidence: 99%